Prevalence and predictors of virological failure and quality of life of people with HIV/AIDS at a Municipal Hospital, Volta Region –Ghana: A cross-sectional study - Kwaku Gyimah Peprah; Faith Agbozo; Mavis Pearl Kwabla; Worlanyo Tashie; Joyce Berkumwin Der (PLoS ONE, 2026)
Background Despite several interventions to eradicate HIV/AIDS globally, virological failure continues to threaten the goals of antiretroviral therapies (ART) and quality of life (QoL) of people with HIV/AIDS (PWHA). This study aimed to assess the prevalence and predictors of virological failure and determine the QoL of PWHA. Methods A cross-sectional study was conducted at the ART clinic of a Municipal Hospital, from June to August 2023, to assess the socio-demographic, medical data, and QoL of PWHA receiving therapy at the clinic. Participants were randomly selected and interviewed: their weight and height were taken and their clinic folders examined to assess virological failure status. Both self-developed structured questionnaire and the WHOQOL-HIV BREF scale (Cronbach alpha = 0.84) were used to assess participants’ data. Bivariate and multiple logistic regression analysis were conducted to determine predictors of virological failure. Also, multiple linear regression was conducted to determine factors influencing QoL of study participants. Results A total of 398 participants comprising of 328 (82.41%) females, and with a mean age of 48.2 years (SD ± 11.71 years), were recruited into the study. The prevalence of virological failure was 6.03%. Factors such as forgetting to take ART (Adjusted Odds Ratio (AOR) = 2.87, 95% Confidence Interval (CI) = 1.02, 7.51; p = 0.04), being classified as baseline WHO clinical staging II (AOR = 6.20, 95% CI = 1.91, 20.04; p = 0.002), and HIV stigmatization (AOR = 3.97, 95% C.I. = 1.1, 14.25; p = 0.035) were associated with virological failure. The overall QoL was good (75.35%). Having no comorbidities (Coefficient of Determination (β) = −2.7, p < 0.0001), having social support (β = 3.94, p < 0.0001) and receiving an average monthly income (β = 2.03, p = 0.002) contributed to good QoL. Conclusion Virological failure in the municipality exceeded the 5.0% target set by the Joint United Nations Programme, despite majority of the study participants presenting with good QoL. The National AIDS Control Programme should consider long-acting injectable therapy for PWHA struggling to adhere to medication.